Polymer solid electrolyte containing lithium trifluoroacetate as well as preparation method and application of polymer solid electrolyte
By preparing a polymer solid electrolyte by combining lithium trifluoroacetate with LiTFSI and PVA, a fluorine-rich interface is constructed, which solves the problem of insufficient electrochemical performance of polymer electrolytes in the prior art. This results in high ionic conductivity and excellent cycle stability, inhibits lithium dendrite growth, and improves the battery life of lithium metal batteries.
Patent Information
- Application Number
- CN202511412539.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-29
- Publication Date
- 2026-01-09
- Estimated Expiration
- 2045-09-29
AI Technical Summary
Existing polymer electrolytes generally have poor electrochemical performance, low ionic conductivity, insufficient cycle stability, and complex preparation methods with poor process controllability.
A polymer solid electrolyte was prepared by combining lithium trifluoroacetate with LiTFSI and PVA. A fluorine-rich interface was constructed in the lithium metal battery through an acid-base neutralization reaction, forming a stable SEI layer dominated by LiF, which improved conductivity and cycle stability.
It significantly improves the cycle stability and ion transport efficiency of lithium metal batteries, suppresses lithium dendrite growth, and enhances the cycle life and stability of the batteries.
Smart Images

Figure CN121307183A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of materials science, and particularly relates to a lithium trifluoroacetate-containing polymer solid-state electrolyte and a preparation method and application thereof. BACKGROUND
[0002] Lithium metal batteries are considered as the ideal choice for the next generation of energy storage devices due to their high energy density. However, its development is limited by key issues such as cycle stability and safety, especially the formation of lithium dendrites and the instability of the electrolyte interface. The continuous side reactions occurring on the interface between the lithium metal anode and the electrolyte can lead to capacity loss and shorten the battery life, while uneven lithium deposition can easily induce dendrite growth, increasing the risk of internal short circuit. In liquid batteries, the solid electrolyte interface (SEI) rich in inorganic components, especially LiF, has been proven to effectively inhibit the generation of lithium dendrites. This is because the weak affinity of LiF with lithium metal (lithiophobicity) makes it difficult for lithium ions to extend as dendrites outside the interface. In addition, the SEI layer rich in LiF has low diffusion energy and high specific surface energy, significantly improving the conductivity of lithium ions and reducing the charge transfer impedance. Studies have shown that the reduction of fluorinated inorganic anions can directly form a SEI layer rich in inorganic components on the surface of lithium metal, while the reduction of fluorine-containing organic anions forms a SEI layer mixed with organic and inorganic components. In addition, in polymer electrolytes, attention must also be paid to the reduction reactions of lithium salts, polymer matrices, and solvents, as the organic components formed by the reduction of solvents may hinder the effective transport and uniform deposition of lithium ions. Therefore, understanding and optimizing the reduction behavior of each component of the electrolyte is crucial to improving the performance of lithium metal batteries. Currently, the existing technology has a main-chain fluorinated polymer electrolyte FEOP prepared based on a multi-fluorine-substituted bis-epoxide cross-linking agent BEPFB, which realizes an interface layer mainly composed of LiF, making it have high ionic conductivity and oxidation stability, suitable for high-voltage cathodes and solid-state lithium metal soft-pack batteries, and exhibits excellent cycle performance and practical prospects (Angewandte Chemie International Edition (DOI: 10.1002 / anie.202424685)), which has the following disadvantages: the lithium ion transference number still needs to be improved, the insufficient lithium ion transference number leads to obvious concentration polarization, it is difficult to inhibit the growth of lithium dendrites during long-term charge and discharge cycles, and the synthesis of fluorine-containing monomers (such as BEPFB) is complex, the raw materials are expensive, large-scale application will bring economic challenges, and perfluorinated compounds may cause environmental persistence problems, in addition, the cross-linked structure, although it enhances the stability, may lead to insufficient toughness of the electrolyte, which may cause battery failure under abuse conditions such as bending. In addition, patent CN118016989A discloses a preparation method of a fluorinated reinforced polymer electrolyte, the polymer electrolyte prepared by the method has a complex preparation method and general electrochemical performance (only about 300 cycles of cycle). SUMMARY
[0003] (I) Objectives of the Invention
[0004] The purpose of the present application is to provide a lithium trifluoroacetate-containing polymer solid electrolyte and its preparation method and application, aiming to solve the technical problems of general electrochemical performance, low ionic conductivity, insufficient cycle stability, complex preparation method and poor process controllability of the polymer electrolyte in the prior art.
[0005] (II) Technical Solutions
[0006] To solve the above problems, the first aspect of the present application provides a preparation method of a lithium trifluoroacetate-containing polymer solid electrolyte, comprising:
[0007] S1, preparation of a lithium hydroxide dispersion: weigh 0.2-0.5 g of lithium hydroxide, dissolve it in 5-10 mL of an alcohol solvent, and place it in a constant temperature condition for ultrasonic treatment to obtain a lithium hydroxide dispersion;
[0008] S2, preparation of lithium trifluoroacetate: add 0.5-2 mL of trifluoroacetic acid solution to the lithium hydroxide dispersion, stir and cool, then place it in a vacuum oven for first drying to obtain a viscous liquid, and then freeze-dry the viscous liquid to obtain powdered lithium trifluoroacetate;
[0009] S3, preparation of a lithium trifluoroacetate-containing polymer solid electrolyte: first, place lithium bis(trifluoromethanesulfonyl)imide LiTFSI and polyethylene glycol in a vacuum oven for second drying, then store them in an inert gas glove box, then weigh 0.1-0.9 g of LiTFSI, 0.2-0.6 g of PVA, and 0.1-0.9 g of lithium trifluoroacetate, mix them together, dissolve the mixture in 15-30 mL of dimethyl sulfoxide, stir uniformly, then place it in a polytetrafluoroethylene mold, and then place it in a vacuum oven for third drying to obtain a lithium trifluoroacetate-containing polymer solid electrolyte. The present application selects lithium trifluoroacetate, which can preferentially decompose to form an inorganic interface layer mainly composed of LiF. This interface structure is dense and has high stability, which is the key to improving the room temperature cycle life of the battery. The strong electronic effect and specific molecular size of the trifluoromethyl group (-CF3) determine its unique decomposition path and final interface composition, which cannot be achieved by other substances. The room temperature cycle test data clearly shows that lithium trifluoroacetate significantly outperforms all comparison substances in terms of capacity retention rate, coulombic efficiency and other key indicators, directly proving the irreplaceability of its effect.
[0010] In addition, the preparation method of lithium trifluoroacetate in the S2 step is specially designed for the application of lithium metal battery electrolyte. There are multiple synthesis paths for lithium trifluoroacetate (for example, metathesis reaction of trifluoroacetic acid and lithium carbonate, or displacement reaction of silver salt thereof and lithium chloride, etc.), but the simple room temperature acid-base neutralization reaction (LiOH + CF3COOH → CF3COOLi + H2O) adopted by the present application is carefully considered. The core reason is that the mild method can effectively avoid the metal impurities or decomposition products introduced by high temperature or complex process; at the same time, by directly reacting in an alcohol solvent, the high purity of the product and the neutrality of the solution can be accurately controlled, thereby maximizing the elimination of the potential hazards of residual acid, base or impurity ions to the stability of the lithium metal negative electrode interface, which is the key to ensuring the excellent cycle life of the battery. Therefore, this synthesis path is an important link to achieve the technical effects of the present application.
[0011] In the present application, LiTFSI, PVA and LiTFA are selected for compounding preparation, which is based on the specific design of complementary functions of the three to build a solid-state electrolyte system with high ionic conductivity and excellent interface stability. LiTFSI provides basic ionic conductivity but poor interface stability, lithium trifluoroacetate compensates for this defect by building a fluorine-rich interface but has insufficient ionic conductivity, and the two need to be strictly proportioned to achieve performance balance. PVA as the matrix has excellent lithium salt dissociation and ion transport, and its dense film-forming property and ether-free structure endow the system with good mechanical strength and electrochemical stability. Experimental data confirm that any deviation of the component ratio from the range will cause interface deterioration or conductivity decline, specifically, when LiTFSI is excessive, the cycle life is attenuated, when lithium trifluoroacetate is excessive, the ionic conductivity is reduced, and when PVA is excessive, the coulombic efficiency is reduced, only within the required range can high ionic conductivity, coulombic efficiency and excellent cycle stability be achieved.
[0012] Preferably, the constant temperature in the S1 step is 20-40℃, the ultrasonic frequency is 30-50 kHz, and the ultrasonic time is 20-50 minutes. According to the actual situation, it can be appropriately prolonged or shortened to ensure complete dispersion. In order to prevent the heat generated during ultrasonic treatment from causing solvent evaporation or unstable reaction conditions, the temperature is set in the range of 20-40℃, and can be kept constant by water bath or cooling device.
[0013] Preferably, in the S2 step, the first drying temperature is 40-80℃, and the first drying time is 6-20 hours, to gently remove the excess alcohol solvent and ensure that the subsequent freeze-drying process can be effectively carried out and avoid solvent crystallization interference.
[0014] Preferably, in the S2 step, the freeze-drying temperature is -40℃ to -80℃, and the freeze-drying time is 30 to 90 hours, so as to ensure that the alcohol solvent possibly remaining after the first drying is completely removed by sublimation at a very low temperature, and the thermal decomposition or residual of the alcohol solvent does not affect the purity of the electrolyte.
[0015] Preferably, in the S3 step, the second drying temperature is 60 to 90℃, and the second drying time is 12 to 24 hours, so as to completely remove the trace amount of water in the lithium salt and the polymer matrix, and ensure that the water content is very low when the battery is assembled, thereby avoiding irreversible damage to the lithium metal negative electrode interface.
[0016] Preferably, the moisture and oxygen in the glove box are both less than 0.1 ppm, and the inert gas includes at least one of nitrogen and argon.
[0017] Preferably, the third drying temperature is 30 to 60℃, and the third drying time is 10 to 20 hours, so as to completely volatilize the dimethyl sulfoxide solvent in the preparation of the lithium trifluoroacetate-containing polymer solid electrolyte, and form a solid electrolyte with complete structure and uniform components.
[0018] Preferably, the alcohol solvent includes methanol, ethanol, butanol or isobutanol.
[0019] The second aspect of the present application provides a lithium trifluoroacetate-containing polymer solid electrolyte obtained by any one of the preparation methods described above.
[0020] The third aspect of the present application provides an application of a lithium trifluoroacetate-containing polymer solid electrolyte in the preparation of a lithium battery, the lithium trifluoroacetate-containing polymer solid electrolyte being obtained by any one of the preparation methods described above.
[0021] (III) Beneficial Effects
[0022] The above technical solution of the present application has the following beneficial technical effects: the present application provides a lithium trifluoroacetate-containing polymer solid electrolyte, a preparation method and an application thereof. The method successfully constructs a fluorine-rich interface by introducing LiTFA into a PSA electrolyte, thereby effectively inhibiting the formation of lithium dendrites and significantly improving the cycle stability of a lithium metal battery. The method first prepares a lithium hydroxide dispersion, then in-situ prepares lithium trifluoroacetate (LiTFA) based on the lithium hydroxide dispersion through an acid-base neutralization reaction, and finally obtains a lithium trifluoroacetate-containing polymer solid electrolyte by mixing and processing corresponding proportions of LiTFSI, PVA and dimethyl sulfoxide with lithium trifluoroacetate. The method completely volatilizes the dimethyl sulfoxide solvent in the preparation of the lithium trifluoroacetate-containing polymer solid electrolyte, and forms a solid electrolyte with complete structure and uniform components. - The high binding energy between TFA and Li + and the high binding energy between TFA- with a higher number of donors, these two factors together make TFA - Anions can effectively enter the solvation sheath of lithium ions. The formation of this structure reduces the migration energy barrier of Li+, while inhibiting ion aggregation, increasing the concentration of free Li+, significantly improving the lithium ion transport efficiency of the electrolyte, thereby improving the ionic conductivity. Studies have shown that the introduction of LiTFA can preferentially occur on the surface of the lithium metal anode, forming a solid-state electrolyte interphase (SEI) layer rich in LiF, effectively improving the cycle life and stability of the battery. BRIEF DESCRIPTION OF DRAWINGS
[0023] Figure 1 is a preparation method flow chart of the lithium trifluoroacetate-containing polymer solid-state electrolyte of the present application;
[0024] Figure 2 is a photo of the polymer solid-state electrolyte obtained in Example 1 of the present application and its processability;
[0025] Figure 3 is a comparison of the surface morphology of the polymer solid-state electrolytes obtained in Examples 1-4 of the present application;
[0026] Figure 4 is the capacity-voltage curve and performance graph of the full battery obtained in Examples 1-10 of the present application. DETAILED DESCRIPTION
[0027] To make the purpose, technical solutions and advantages of the present application clearer and more explicit, the present application is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present application. In addition, in the following description, the description of well-known structures and techniques is omitted to avoid unnecessary confusion of the concept of the present application.
[0028] Example 1
[0029] (1) Preparation of lithium hydroxide dispersion
[0030] First, accurately weigh 0.3 g of lithium hydroxide (LiOH) and slowly add it to 10 mL of methanol solution. After adding lithium hydroxide, use an ultrasonic device to treat the solution thoroughly to ensure that the lithium hydroxide is uniformly dispersed in the solvent. The frequency of the ultrasonic device is set to 40 kHz, the treatment time is controlled to 30 minutes, the ultrasonic temperature is set to 30℃, and it can be kept constant by water bath or cooling device. After the ultrasonic treatment is completed, the solution should be observed to see if it has become a uniform, non-particulate dispersion state, ensuring that it is suitable for subsequent reaction or preparation steps.
[0031] (2) Preparation of lithium trifluoroacetate (LiTFA)
[0032] Slowly add 0.932 mL of trifluoroacetic acid solution into the lithium hydroxide ultrasonic dispersion solution obtained in step (1), and gently shake or stir while adding until the solution becomes clear and transparent. To ensure sufficient reaction, the dropping speed should be kept slow and continuous stirring should be maintained to prevent local concentration from being too high and causing uneven reaction. After the solution cools to room temperature, it is placed in a 70°C vacuum oven to dry for 12 hours until a viscous liquid is formed. Then, the viscous liquid is transferred to a freeze dryer and dried at -50°C for 48 hours until it is completely dried into a uniform powder of lithium trifluoroacetate. The resulting product should be protected from exposure to air to prevent moisture absorption from affecting subsequent use.
[0033] (3) Lithium trifluoroacetate-containing polymer solid-state electrolyte (LiTFA-based polymer solid-state electrolyte, abbreviated as PSA-1)
[0034] Before preparing the electrolyte, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and polyethylene glycol (PVA) are dried in a 70°C vacuum oven for 15 hours. They are then stored in an inert gas glove box with moisture and oxygen levels below 0.1 ppm. To prepare the PSA solid-state electrolyte, 0.4 g of PVA, 0.6 g of LiTFSI, 0.4 g of LiTFA, and 15 mL of dimethyl sulfoxide (DMSO) are weighed in the glove box and stirred at 60°C and 800 rpm overnight. The uniform mixture is placed in a polytetrafluoroethylene mold and dried in a 50°C vacuum oven for more than 12 hours to obtain the PSA-1 electrolyte. Figure 2 -a indicates that the electrolyte is in the form of a milky white disc, Figure 2 -b indicates that the electrolyte has good mechanical flexibility and can effectively inhibit lithium dendrite from piercing the electrolyte during cycling, improving the long cycle life of the battery.
[0035] Example 2
[0036] (1) Preparation of lithium hydroxide dispersion
[0037] First, accurately weigh 0.3 g of lithium hydroxide (LiOH) and slowly add it to 10 mL of an alcohol solvent. After adding the lithium hydroxide, use an ultrasonic device to treat the solution thoroughly to ensure that the lithium hydroxide is uniformly dispersed in the solvent. The frequency of the ultrasonic device is set to 40 kHz, the treatment time is controlled to 30 minutes, and the ultrasonic temperature is set to 30°C, which can be maintained constant by water bath or cooling device. After the ultrasonic treatment is completed, the solution should be observed to see if it has become a uniform, non-granular dispersion state to ensure that it is suitable for subsequent reaction or preparation steps.
[0038] (2) Preparation of lithium trifluoroacetate (LiTFA)
[0039] To the lithium hydroxide dispersion obtained in step (1), 0.932 mL of trifluoroacetic acid solution was slowly added while gently shaking or stirring until the solution became clear and transparent. To ensure complete reaction, the dropping speed should be kept slow and continuous stirring should be maintained to prevent local over-concentration and uneven reaction. After the solution cooled to room temperature, it was placed in a vacuum oven at 70°C for 12 hours until a viscous liquid was formed. Then, the viscous liquid was transferred to a freeze dryer and dried at -50°C for 48 hours until it was completely dried into a uniform powder of lithium trifluoroacetate. The resulting product should be kept away from air to prevent moisture absorption and affect subsequent use.
[0040] (3) Preparation of lithium TFA-based polymer with solid-state electrolyte (PSA-2)
[0041] Before preparing the electrolyte, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), polyethylene glycol (PVA) were dried in a vacuum oven at 70°C for 15 hours. And stored in a glove box inert gas. The moisture and oxygen in the glove box are both less than 0.1 ppm. To prepare the PSA solid-state electrolyte, 0.4 g of PVA, 0.5 g of LiTFSI, 0.5 g of LiTFA and 15 ml of dimethyl sulfoxide (DMSO) were weighed in sequence in the glove box, and stirred at 60°C and 800 rpm overnight. The uniform mixture was placed in a polytetrafluoroethylene mold, and the PSA-2 electrolyte was obtained by drying in a vacuum oven at 50°C for more than 12 hours.
[0042] Example 3
[0043] (1) Preparation of lithium hydroxide dispersion
[0044] First, 0.3 g of lithium hydroxide (LiOH) was accurately weighed and slowly added to 10 mL of an alcohol solvent, which can be any one of methanol, ethanol, butanol or isobutanol, and the specific choice can be adjusted according to experimental requirements. After adding lithium hydroxide, the solution was treated with an ultrasonic device to ensure that lithium hydroxide was uniformly dispersed in the solvent. The frequency of the ultrasonic device was set to 40 kHz, the treatment time was controlled to 30 minutes, the ultrasonic temperature was set to 30°C, and the temperature was kept constant by water bath or cooling device. After the ultrasonic treatment was completed, it should be observed whether the solution had become a uniform, non-particulate dispersion state to ensure that it was suitable for subsequent reaction or preparation steps.
[0045] (2) Preparation of lithium trifluoroacetate (LiTFA)
[0046] To the lithium hydroxide dispersion obtained in step (1), 0.932 mL of trifluoroacetic acid solution was slowly added while gently shaking or stirring until the solution became clear and transparent. To ensure complete reaction, the dropping speed should be kept slow and continuous stirring should be maintained to prevent local over-concentration and uneven reaction. After the solution cooled to room temperature, it was placed in a vacuum oven at 70°C for 12 hours until a viscous liquid was formed. Then, the viscous liquid was transferred to a freeze dryer and dried at -50°C for 48 hours until it was completely dried into a uniform powder of lithium trifluoroacetate. The product should be kept away from air to prevent moisture absorption and affect subsequent use.
[0047] (3) Preparation of lithium TFA-based polymer with solid-state electrolyte (PSA-3)
[0048] Before preparing the electrolyte, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), polyethylene glycol (PVA) were dried in a vacuum oven at 70°C for 15 hours. And stored in a glove box with inert gas. The moisture and oxygen in the glove box were both below 0.1 ppm. To prepare the PSA solid-state electrolyte, 0.4 g of PVA, 0.4 g of LiTFSI, 0.6 g of LiTFA and 15 mL of dimethyl sulfoxide (DMSO) were weighed in sequence in the glove box, and stirred at 60°C and 800 rpm overnight. The uniform mixture was placed in a polytetrafluoroethylene mold, and the PSA-3 electrolyte was obtained by drying in a vacuum oven at 50°C for more than 12 hours.
[0049] Example 4
[0050] (1) Preparation of lithium hydroxide dispersion
[0051] First, 0.3 g of lithium hydroxide (LiOH) was accurately weighed and slowly added to 10 mL of methanol solution. After adding lithium hydroxide, the solution was treated with an ultrasonic device to ensure that lithium hydroxide was uniformly dispersed in the solvent. The frequency of the ultrasonic device was set to 40 kHz, the treatment time was controlled to 30 minutes, the ultrasonic temperature was set to 30°C, and the temperature was kept constant by water bath or cooling device. After the ultrasonic treatment was completed, the solution should be observed to see if it has become a uniform, non-particulate dispersion state to ensure that it is suitable for subsequent reaction or preparation steps.
[0052] (2) Preparation of lithium trifluoroacetate (LiTFA)
[0053] To the lithium hydroxide dispersion obtained in step (1), 0.932 mL of trifluoroacetic acid solution was slowly added while gently shaking or stirring until the solution became clear and transparent. To ensure complete reaction, the dropping speed should be kept slow and continuous stirring should be maintained to prevent local over-concentration and uneven reaction. After the solution cooled to room temperature, it was placed in a vacuum oven at 70°C for 12 hours until a viscous liquid was formed. Then, the viscous liquid was transferred to a freeze dryer and dried at -50°C for 48 hours until it was completely dried into a uniform powder of lithium trifluoroacetate. The product should be kept away from air to prevent moisture absorption and affect subsequent use.
[0054] (3) Preparation of lithium TFA-based polymer with solid-state electrolyte (PSA-4)
[0055] Before preparing the electrolyte, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), polyethylene glycol (PVA) were dried in a vacuum oven at 70°C for 15 hours. And stored in a glove box with inert gas. The moisture and oxygen in the glove box were both below 0.1 ppm. To prepare the PSA solid-state electrolyte, 0.4 g of PVA, 0.3 g of LiTFSI, 0.7 g of LiTFA and 15 mL of dimethyl sulfoxide (DMSO) were weighed in sequence in the glove box, and stirred at 60°C and 800 rpm overnight. The uniform mixture was placed in a polytetrafluoroethylene mold, and the PSA-4 electrolyte was obtained by drying in a vacuum oven at 50°C for more than 12 hours.
[0056] Example 5
[0057] (1) Preparation of lithium hydroxide dispersion
[0058] First, 0.3 g of lithium hydroxide (LiOH) was accurately weighed and slowly added to 10 mL of methanol solution. After adding lithium hydroxide, the solution was treated with an ultrasonic device to ensure that lithium hydroxide was uniformly dispersed in the solvent. The frequency of the ultrasonic device was set to 40 kHz, the treatment time was controlled to 30 minutes, the ultrasonic temperature was set to 30°C, and the temperature was kept constant by water bath or cooling device. After the ultrasonic treatment was completed, the solution should be observed to see if it has become a uniform, non-particulate dispersion state to ensure that it is suitable for subsequent reaction or preparation steps.
[0059] (2) Preparation of lithium trifluoroacetate (LiTFA)
[0060] To the lithium hydroxide dispersion obtained in step (1), 0.932 mL of trifluoroacetic acid solution was slowly added while gently shaking or stirring until the solution became clear and transparent. To ensure complete reaction, the dropping speed should be kept slow and continuous stirring should be maintained to prevent local over-concentration and uneven reaction. After the solution cooled to room temperature, it was placed in a vacuum oven at 70°C for 12 hours until a viscous liquid was formed. Then, the viscous liquid was transferred to a freeze dryer and dried at -50°C for 48 hours until it was completely dried into a uniform powder of lithium trifluoroacetate. The product should be kept away from air to prevent moisture absorption and affect subsequent use.
[0061] (3) Preparation of lithium TFA-based polymer with solid-state electrolyte (PSA-5)
[0062] Before preparing the electrolyte, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), polyethylene glycol (PVA) were dried in a vacuum oven at 70°C for 15 hours. And stored in a glove box with inert gas. The moisture and oxygen in the glove box were both below 0.1 ppm. To prepare the PSA solid-state electrolyte, 0.4 g of PVA, 0.2 g of LiTFSI, 0.8 g of LiTFA and 15 mL of dimethyl sulfoxide (DMSO) were weighed in sequence in the glove box, and stirred at 60°C and 800 rpm overnight. The uniform mixture was placed in a polytetrafluoroethylene mold, and the PSA-5 electrolyte was obtained by drying in a vacuum oven at 50°C for more than 12 hours.
[0063] Example 6
[0064] (1) Preparation of lithium hydroxide dispersion
[0065] First, 0.3 g of lithium hydroxide (LiOH) was accurately weighed and slowly added to 10 mL of methanol solution. After adding lithium hydroxide, the solution was treated with an ultrasonic device to ensure that lithium hydroxide was uniformly dispersed in the solvent. The frequency of the ultrasonic device was set to 40 kHz, the treatment time was controlled to 30 minutes, the ultrasonic temperature was set to 30°C, and the temperature was kept constant by water bath or cooling device. After the ultrasonic treatment was completed, the solution should be observed to see if it has become a uniform, non-particulate dispersion state to ensure that it is suitable for subsequent reaction or preparation steps.
[0066] (2) Preparation of lithium trifluoroacetate (LiTFA)
[0067] To the lithium hydroxide dispersion obtained in step (1), 0.932 mL of trifluoroacetic acid solution was slowly added while gently shaking or stirring until the solution became clear and transparent. To ensure complete reaction, the dropping speed should be kept slow and continuous stirring should be maintained to prevent local over-concentration and uneven reaction. After the solution cooled to room temperature, it was placed in a vacuum oven at 70°C for 12 hours until a viscous liquid was formed. Then, the viscous liquid was transferred to a freeze dryer and dried at -50°C for 48 hours until it was completely dried into a uniform powder of lithium trifluoroacetate. The product should be kept away from air to prevent moisture absorption and affect subsequent use.
[0068] (3) Preparation of lithium TFA-based polymer with solid-state electrolyte (PSA-6)
[0069] Before preparing the electrolyte, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), polyethylene glycol (PVA) were dried in a vacuum oven at 70°C for 15 hours. And stored in a glove box with inert gas. The moisture and oxygen in the glove box were both below 0.1 ppm. To prepare the PSA solid-state electrolyte, 0.4 g of PVA, 0.1 g of LiTFSI, 0.9 g of LiTFA and 15 mL of dimethyl sulfoxide (DMSO) were weighed in sequence in the glove box, and stirred at 60°C and 800 rpm overnight. The uniform mixture was placed in a polytetrafluoroethylene mold, and the PSA-6 electrolyte was obtained by drying in a vacuum oven at 50°C for more than 12 hours.
[0070] Example 7
[0071] (1) Preparation of lithium hydroxide dispersion
[0072] First, 0.3 g of lithium hydroxide (LiOH) was accurately weighed and slowly added to 10 mL of methanol solution. After adding lithium hydroxide, the solution was treated with an ultrasonic device to ensure that lithium hydroxide was uniformly dispersed in the solvent. The frequency of the ultrasonic device was set to 40 kHz, the treatment time was controlled to 30 minutes, the ultrasonic temperature was set to 30°C, and the temperature was kept constant by water bath or cooling device. After the ultrasonic treatment was completed, the solution should be observed to see if it has become a uniform, non-particulate dispersion state to ensure that it is suitable for subsequent reaction or preparation steps.
[0073] (2) Preparation of lithium trifluoroacetate (LiTFA)
[0074] To the lithium hydroxide dispersion obtained in step (1), 0.932 mL of trifluoroacetic acid solution was slowly added while gently shaking or stirring until the solution became clear and transparent. To ensure complete reaction, the dropping speed should be kept slow and continuous stirring should be maintained to prevent local over-concentration and uneven reaction. After the solution cooled to room temperature, it was placed in a vacuum oven at 70°C for 12 hours until a viscous liquid was formed. Then, the viscous liquid was transferred to a freeze dryer and dried at -50°C for 48 hours until it was completely dried into a uniform powder of lithium trifluoroacetate. The product should be kept away from air to prevent moisture absorption and affect subsequent use.
[0075] (3) Preparation of lithium TFA-based polymer with solid-state electrolyte (PSA-7)
[0076] Before preparing the electrolyte, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), polyethylene glycol (PVA) were dried in a vacuum oven at 70°C for 15 hours. And stored in a glove box with inert gas. The moisture and oxygen in the glove box were both below 0.1 ppm. To prepare the PSA solid-state electrolyte, 0.4 g of PVA, 0.7 g of LiTFSI, 0.3 g of LiTFA and 15 mL of dimethyl sulfoxide (DMSO) were weighed in sequence in the glove box, and stirred at 60°C and 800 rpm overnight. The uniform mixture was placed in a polytetrafluoroethylene mold, and the PSA-7 electrolyte was obtained by drying in a vacuum oven at 50°C for more than 12 hours.
[0077] Example 8
[0078] (1) Preparation of lithium hydroxide dispersion
[0079] First, 0.3 g of lithium hydroxide (LiOH) was accurately weighed and slowly added to 10 mL of methanol solution. After adding lithium hydroxide, the solution was treated with an ultrasonic device to ensure that lithium hydroxide was uniformly dispersed in the solvent. The frequency of the ultrasonic device was set to 40 kHz, the treatment time was controlled to 30 minutes, the ultrasonic temperature was set to 30°C, and the temperature was kept constant by water bath or cooling device. After the ultrasonic treatment was completed, the solution should be observed to see if it has become a uniform, non-particulate dispersion state to ensure that it is suitable for subsequent reaction or preparation steps.
[0080] (2) Preparation of lithium trifluoroacetate (LiTFA)
[0081] To the lithium hydroxide dispersion obtained in step (1), 0.932 mL of trifluoroacetic acid solution was slowly added while gently shaking or stirring until the solution became clear and transparent. To ensure complete reaction, the dropping speed should be kept slow and continuous stirring should be maintained to prevent local over-concentration and uneven reaction. After the solution cooled to room temperature, it was placed in a vacuum oven at 70°C for 12 hours until a viscous liquid was formed. Then, the viscous liquid was transferred to a freeze dryer and dried at -50°C for 48 hours until it was completely dried into a uniform powder of lithium trifluoroacetate. The product should be kept away from air to prevent moisture absorption and affect subsequent use.
[0082] (3) Preparation of lithium TFA-based polymer with solid-state electrolyte (PSA-8)
[0083] Before preparing the electrolyte, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), polyethylene glycol (PVA) were dried in a vacuum oven at 70°C for 15 hours. And stored in a glove box with inert gas. The moisture and oxygen in the glove box were both less than 0.1 ppm. To prepare the PSA solid-state electrolyte, 0.4 g of PVA, 0.8 g of LiTFSI, 0.2 g of LiTFA and 15 mL of dimethyl sulfoxide (DMSO) were weighed in sequence in the glove box, and stirred at 60°C and 800 rpm overnight. The uniform mixture was placed in a polytetrafluoroethylene mold, and the PSA-8 electrolyte was obtained by drying in a vacuum oven at 50°C for more than 12 hours.
[0084] Example 9
[0085] (1) Preparation of lithium hydroxide dispersion
[0086] First, 0.3 g of lithium hydroxide (LiOH) was accurately weighed and slowly added to 10 mL of methanol solution. After adding lithium hydroxide, the solution was treated with an ultrasonic device to ensure that lithium hydroxide was uniformly dispersed in the solvent. The frequency of the ultrasonic device was set to 40 kHz, the treatment time was controlled to 30 minutes, the ultrasonic temperature was set to 30°C, and the temperature was kept constant by water bath or cooling device. After the ultrasonic treatment was completed, the solution should be observed to see if it has become a uniform, non-particulate dispersion state to ensure that it is suitable for subsequent reaction or preparation steps.
[0087] (2) Preparation of lithium trifluoroacetate (LiTFA)
[0088] To the lithium hydroxide dispersion obtained in step (1), 0.932 mL of trifluoroacetic acid solution was slowly added while gently shaking or stirring until the solution became clear and transparent. To ensure complete reaction, the dropping speed should be kept slow and continuous stirring should be maintained to prevent local over-concentration and uneven reaction. After the solution cooled to room temperature, it was placed in a vacuum oven at 70°C for 12 hours until a viscous liquid was formed. Then, the viscous liquid was transferred to a freeze dryer and dried at -50°C for 48 hours until it was completely dried into a uniform powder of lithium trifluoroacetate. The product should be kept away from air to prevent moisture absorption and affect subsequent use.
[0089] (3) Preparation of lithium TFA-based polymer with solid-state electrolyte (PSA-9)
[0090] Before preparing the electrolyte, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), polyethylene glycol (PVA) were dried in a vacuum oven at 70°C for 15 hours. And stored in a glove box with inert gas. The moisture and oxygen in the glove box were both below 0.1 ppm. To prepare the PSA solid-state electrolyte, 0.4 g of PVA, 0.9 g of LiTFSI, 0.1 g of LiTFA and 15 mL of dimethyl sulfoxide (DMSO) were weighed in sequence in the glove box, and stirred at 60°C and 800 rpm overnight. The uniform mixture was placed in a polytetrafluoroethylene mold, and the PSA-9 electrolyte was obtained by drying in a vacuum oven at 50°C for more than 12 hours.
[0091] Example 10
[0092] (1) Preparation of lithium hydroxide dispersion
[0093] First, 0.3 g of lithium hydroxide (LiOH) was accurately weighed and slowly added to 10 mL of methanol solution. After adding lithium hydroxide, the solution was treated with an ultrasonic device to ensure that lithium hydroxide was uniformly dispersed in the solvent. The frequency of the ultrasonic device was set to 40 kHz, the treatment time was controlled to 30 minutes, the ultrasonic temperature was set to 30°C, and the temperature was kept constant by water bath or cooling device. After the ultrasonic treatment was completed, the solution should be observed to see if it has become a uniform, non-particulate dispersion state to ensure that it is suitable for subsequent reaction or preparation steps.
[0094] (2) Preparation of lithium trifluoroacetate (LiTFA)
[0095] To the lithium hydroxide ultrasonic dispersion obtained in step (1), 0.932 mL of trifluoroacetic acid solution was slowly added while gently shaking or stirring until the solution became clear and transparent. To ensure complete reaction, the dropping speed should be kept slow and continuous stirring should be maintained to prevent uneven reaction caused by excessive local concentration. After the solution cooled to room temperature, it was placed in a vacuum oven at 70 °C for 12 hours until a viscous liquid was formed. Then, the viscous liquid was transferred to a freeze dryer and dried at -50 °C for 48 hours until it was completely dried into a uniform powder of lithium trifluoroacetate. The product should be kept from exposure to air to prevent moisture absorption affecting subsequent use.
[0096] (3) Preparation of lithium TFA-based polymer solid-state electrolyte (PSA-10)
[0097] Before preparing the electrolyte, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and polyvinyl alcohol (PVA) were dried in a vacuum oven at 70 °C for 15 hours. They were then stored in an inert gas glovebox. The moisture and oxygen in the glovebox were both less than 0.1 ppm. To prepare the PSA solid-state electrolyte, 0.5 g of PVA, 0.6 g of LiTFSI, 0.4 g of LiTFA, and 15 mL of dimethyl sulfoxide (DMSO) were weighed in the glovebox and stirred at 60 °C and 800 rpm overnight. The uniform mixture was placed in a polytetrafluoroethylene mold and dried in a vacuum oven at 50 °C for more than 12 hours to obtain the PSA-10 electrolyte.
[0098] Comparative Example 1
[0099] Unlike Example 1, only lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was added in Comparative Example 1. Before preparing the electrolyte, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and polyvinyl alcohol (PVA) were dried in a vacuum oven at 70 °C for 15 hours. They were then stored in an inert gas glovebox. The moisture and oxygen in the glovebox were both less than 0.1 ppm. To prepare the PSA solid-state electrolyte, 0.4 g of PVA, 1 g of LiTFSI, and 15 mL of dimethyl sulfoxide (DMSO) were weighed in the glovebox and stirred at 60 °C and 800 rpm overnight. The uniform mixture was placed in a polytetrafluoroethylene mold and dried in a vacuum oven at 50 °C for 12 hours to obtain the PSA solid-state electrolyte.
[0100] Comparative Example 2
[0101] Unlike Example 2, only lithium trifluoroacetate (LiTFA) was added in Comparative Example 2. Before preparing the electrolyte, lithium trifluoroacetate (LiTFA), polyvinyl alcohol (PVA) were dried in a vacuum oven at 70 °C for 15 hours. And stored in a glove box under inert gas. The moisture and oxygen in the glove box were both below 0.1 ppm. To prepare the PA solid-state electrolyte, 0.4 g of PVA, 1 g of LiTFA and 15 ml of dimethyl sulfoxide (DMSO) were weighed in sequence in the glove box, and stirred at 800 rpm at 60 °C overnight. The uniform mixture was placed in a polytetrafluoroethylene mold, and dried in a vacuum oven at 50 °C for 12 hours to obtain the PA solid-state electrolyte.
[0102] Comparative Example 3
[0103] (1) Preparation of lithium hydroxide dispersion
[0104] First, 0.3 g of lithium hydroxide (LiOH) was accurately weighed and slowly added to 10 mL of methanol solution. After adding lithium hydroxide, the solution was treated with an ultrasonic device to ensure that lithium hydroxide was uniformly dispersed in the solvent. The frequency of the ultrasonic device was set to 40 kHz, the treatment time was controlled to 30 minutes, the ultrasonic temperature was set to 30 °C, and the temperature was kept constant by water bath or cooling device. After the ultrasonic treatment was completed, it should be observed whether the solution had become a uniform, non-particulate dispersion state, ensuring that it was suitable for subsequent reaction or preparation steps.
[0105] (2) Preparation of lithium tetrafluoropropionate (LiTFPA)
[0106] The lithium hydroxide ultrasonic dispersion obtained in step (1) was slowly added with 1.17 mL of tetrafluoropropionic acid solution, and was slightly shaken or stirred during the addition until the solution became clear and transparent. To ensure complete reaction, the addition speed should be slow and continuous stirring should be maintained to prevent local concentration from being too high and causing uneven reaction. After the solution cooled to room temperature, it was placed in a vacuum oven at 70 °C for 12 hours until a viscous liquid was formed. Then, the viscous liquid was transferred to a freeze dryer and dried at -50 °C for 48 hours until it was completely dried into a uniform powder of lithium trifluoroacetate. The product obtained should be protected from exposure to air to prevent moisture from affecting subsequent use.
[0107] (3) Preparation of LiTFPA-based polymer solid-state electrolyte (PSP)
[0108] Before preparing the electrolyte, lithium tetrafluoropropionate (LiTFPA) and polyethylene glycol (PVA) were dried in a vacuum oven at 70 °C for 15 hours. And stored in a glove box under inert gas. The moisture and oxygen in the glove box were both below 0.1 ppm. To prepare the PSA solid-state electrolyte, 0.4 g of PVA, 0.6 g of LiTFPA, 0.4 g of LiTFA and 15 ml of dimethyl sulfoxide (DMSO) were weighed in sequence in the glove box, and stirred at 60 °C and 800 rpm overnight. The uniform mixture was placed in a polytetrafluoroethylene mold, and dried in a vacuum oven at 50 °C for more than 12 hours to obtain the PSP electrolyte.
[0109] Comparative Example 4
[0110] (1) Preparation of lithium hydroxide dispersion
[0111] First, 0.3 g of lithium hydroxide (LiOH) was accurately weighed and slowly added to 10 mL of methanol solution. After adding lithium hydroxide, the solution was treated with an ultrasonic device to ensure that lithium hydroxide was uniformly dispersed in the solvent. The frequency of the ultrasonic device was set to 40 kHz, the treatment time was controlled to 30 minutes, the ultrasonic temperature was set to 30 °C, and the temperature was kept constant by water bath or cooling device. After the ultrasonic treatment was completed, it should be observed whether the solution had become a uniform, non-particulate dispersion state, ensuring that it was suitable for subsequent reaction or preparation steps.
[0112] (2) Preparation of lithium pentafluoropropionate (LiPFPA)
[0113] The lithium hydroxide ultrasonic dispersion solution obtained in step (1) was slowly added with 1.32 mL of pentafluoropropionic acid solution, and was slightly shaken or stirred during the addition until the solution became clear and transparent. To ensure sufficient reaction, the addition speed should be kept slow and continuous stirring should be maintained to prevent local concentration from being too high and causing uneven reaction. After the solution cooled to room temperature, it was placed in a vacuum oven at 70 °C for 12 hours until a viscous liquid was formed. Then, the viscous liquid was transferred to a freeze dryer and dried at -50 °C for 48 hours until it was completely dried into a uniform powder of lithium trifluoroacetate. The product should be protected from exposure to air to prevent moisture from affecting subsequent use.
[0114] (3) Preparation of LiPFPA-based polymer solid-state electrolyte (PSF)
[0115] Before preparing the electrolyte, lithium pentafluoropropionate (LiPFPA) and polyethylene glycol (PVA) were dried in a vacuum oven at 70 °C for 15 hours. And stored in the glove box under inert gas. The moisture and oxygen in the glove box were both below 0.1 ppm. To prepare the PSA solid-state electrolyte, 0.4 g PVA, 0.6 g LiPFPA, 0.4 g LiTFA and 15 ml dimethyl sulfoxide (DMSO) were weighed in the glove box in turn, and stirred at 60 °C and 800 rpm overnight. The uniform mixture was placed in a polytetrafluoroethylene mold, and the PSF electrolyte was obtained by drying in a vacuum oven at 50 °C for more than 12 hours.
[0116] Figure 3 In the figure, the contrast of a-d shows that the electrolyte surface without lithium plating stripping treatment is relatively smooth. It is shown that the surface of PSA-1 electrolyte is more uniform than that of PSA-2 electrolyte, PSA-3 electrolyte and PSA-4 electrolyte, and has fewer cracks, which not only increases the contact area with the lithium negative electrode and the positive electrode, but also provides favorable conditions for the uniform deposition of lithium ions. Figures e-l are the surface morphology of the electrolyte and the electrode after cycling. The surface morphology of PSA-1 electrolyte after cycling can hardly be observed. Similarly, the surface of the lithium negative electrode remains relatively smooth and flat as a whole. However, in the case of PSA-2 electrolyte, lithium dendrites grow significantly on the surface of the electrolyte and the lithium negative electrode, which is manifested as a large amount of uneven lithium deposition. PSA-3 and PSA-4 electrolytes also show similar phenomena. Therefore, compared with PSA-2 electrolyte, PSA-3 electrolyte and PSA-4 electrolyte, PSA-1 electrolyte shows better effect in inhibiting the growth of lithium dendrites. Figure 4 In the figure, a and b are the capacity-voltage curves of the full cells of PSA-2 and PSA-1 respectively; (c) represents the performance of PSA-1-PSA-10 full cells at 0.5 C. Figures a and b show that as the number of cycles exceeds 200 times, the PSA-1 full cell can maintain a relatively stable charge-discharge voltage platform, while the charge-discharge platform curve of the PSA-2 full cell has obviously changed into an arc shape, accompanied by a sharp decrease in capacity. This observation indicates that although the PSA-1 full cell shows a higher overpotential in the initial cycle, it exhibits better stability and battery performance in the long-term cycle. On the contrary, although the PSA-2 full cell has a lower initial overpotential, its stability of the charge-discharge platform is poor, which ultimately leads to a significant decrease in capacity.
[0117] The electrochemical performance of Figure c clearly shows the influence of different PSA systems on battery performance. At 0.5C rate, PSA-1 full battery shows the best overall performance, with an initial capacity of 145.3 mAh / g, a capacity retention rate of up to 88.7% after 500 cycles, and a coulombic efficiency always above 99.9%. This result shows that the optimized electrolyte composition can establish a stable lithium ion transport solvation structure, promote the formation of a dense and inorganic fluoride-rich SEI layer, effectively inhibit lithium dendrite growth, and achieve efficient lithium deposition / stripping process.
[0118] In contrast, although the PSA-2 full battery has a higher initial capacity of 151.4 mAh / g, its average coulombic efficiency is only 97.12%, and the capacity retention rate is less than 80%, which shows that the SEI layer structure formed is loose and rich in organic components, and cannot effectively prevent the continuous occurrence of interface side reactions. The PSA-3 full battery has an initial capacity of only 102.9 mAh / g due to the high intrinsic impedance of the electrolyte, showing a serious limitation of ion transport kinetics. In PSA-4 to PSA-5 systems, as the proportion of LiTFA increases, the battery capacity shows a downward trend; while the proportion of LiTFSI increases (PSA-6 to PSA-9), although the initial capacity remains at a high level, the decline in interface stability leads to rapid capacity decay. The increase of PVA content in Example 10 leads to a significant decrease in the ionic conductivity of the system. These comparative results fully demonstrate the equal importance of electrolyte component balance in achieving high ionic conductivity and stable interface layer, and any deviation of any component will lead to a significant decline in battery performance.
[0119] At the same time, according to the comparative analysis of the data in Table 2, Comparative Example 1 (PS system) has the highest conductivity, but the capacity retention rate after 200 cycles is only 80.6%, which proves that a single lithium salt system cannot balance high ionic conduction and interface stability; Comparative Example 2 (PA system) is limited by the extremely low ionic conductivity, and its actual capacity and cycle performance are not good; Comparative Example 3 (PSP system) and Comparative Example 4 (PSF system) have a capacity retention rate of 84.2% and 85.4% respectively after 400 cycles, which is better than Comparative Examples 1 and 2, but still significantly lower than Example 1, and the cycle period is shorter. These comparative results fully verify the synergistic effect of the LiTFSI and LiTFA dual salt system and the PVA matrix: the balanced structure achieved by precise proportioning can not only maintain sufficient ionic conductivity, but also build a stable electrode / electrolyte interface, thereby significantly improving the long cycle life of the battery.
[0120] Table 1 Comparison of battery electrochemical performance of Examples 1-10
[0121]
[0122] Table 2. Comparison of battery electrochemical performance of Comparative Examples 1-4 (including Example 1)
[0123]
[0124] It should be understood that the foregoing detailed description of the application, rather than limiting the application, is intended to explain and describe the current implementation of the application. Any modification, equivalent replacement, or improvement made without departing from the spirit and scope of the application should be included in the protection scope of the application. In addition, the appended claims of the application are intended to cover all changes and modifications falling within the scope and boundary of the appended claims, or the equivalent forms of such scope and boundary.
Claims
1. A method for preparing a polymer solid electrolyte containing lithium trifluoroacetate, characterized in that, include: S1, Preparation of lithium hydroxide dispersion: Weigh 0.2-0.5g of lithium hydroxide, dissolve it in 5-10mL of alcohol solvent, and sonicate it under constant temperature to obtain lithium hydroxide dispersion. S2, Preparation of lithium trifluoroacetate: 0.5-2 mL of trifluoroacetic acid solution is added dropwise to the lithium hydroxide dispersion, stirred, cooled, and then placed in a vacuum oven for the first drying to obtain a viscous liquid. The viscous liquid is then freeze-dried to obtain powdered lithium trifluoroacetate. S3, Preparation of polymer solid electrolyte containing lithium trifluoroacetate: First, LiTFSI and PVA were dried a second time in a vacuum oven and then stored in an inert gas glove box. Then, 0.1-0.9g of LiTFSI, 0.2-0.6g of PVA and 0.1-0.9g of powdered lithium trifluoroacetate were weighed and mixed. The mixture was dissolved in 15-30ml of dimethyl sulfoxide, stirred evenly, placed in a polytetrafluoroethylene mold, and then placed in a vacuum oven for a third drying to obtain the polymer solid electrolyte containing lithium trifluoroacetate.
2. The method for preparing the polymer solid electrolyte containing lithium trifluoroacetate according to claim 1, characterized in that, In step S1, the constant temperature is 20–40°C, the ultrasonic frequency is 30–50 kHz, and the ultrasonic time is 20–50 minutes.
3. The method for preparing the polymer solid electrolyte containing lithium trifluoroacetate according to claim 1, characterized in that, In step S2, the first drying temperature is 40–80°C, and the first drying time is 6–20 hours.
4. The method for preparing the polymer solid electrolyte containing lithium trifluoroacetate according to claim 1, characterized in that, In step S2, the freeze-drying temperature is -40℃ to -80℃, and the freeze-drying time is 30 to 90 hours.
5. The method for preparing the polymer solid electrolyte containing lithium trifluoroacetate according to claim 1, characterized in that, In step S3, the second drying temperature is 60–90°C, and the second drying time is 12–24 hours.
6. The method for preparing the polymer solid electrolyte containing lithium trifluoroacetate according to claim 1, characterized in that, The glove box has a moisture and oxygen content of less than 0.1 ppm, and the inert gas includes at least one of nitrogen and argon.
7. The method for preparing the polymer solid electrolyte containing lithium trifluoroacetate according to claim 1, characterized in that, The third drying temperature is 30-60℃, and the third drying time is 10-20 hours.
8. The method for preparing the polymer solid electrolyte containing lithium trifluoroacetate according to claim 1, characterized in that, The alcohol solvents include methanol, ethanol, butanol, or isobutanol.
9. A polymer solid electrolyte containing lithium trifluoroacetate, characterized in that, The polymer solid electrolyte containing lithium trifluoroacetate is obtained by the preparation method according to any one of claims 1-8.
10. The application of a polymer solid electrolyte containing lithium trifluoroacetate in the preparation of lithium batteries, characterized in that, The polymer solid electrolyte containing lithium trifluoroacetate is obtained by the preparation method according to any one of claims 1-8.
Citation Information
Patent Citations
Fluorination-enhanced composite polymer electrolyte as well as preparation method and application thereof
CN118016989A
PEO-matrix gel polymer electrolyte and preparation method thereof
CN103456518A
Gel polymer electrolyte and preparation method thereof
CN103811807A
Solid-state polymer electrolyte, preparation method thereof and solid-state lithium metal battery
CN114725501A